Mesenchymal Stem Cell-Derived Antimicrobial Peptides as Potential Anti-Neoplastic Agents: New Insight into Anticancer Mechanisms of Stem Cells and Exosomes - Kasra Moeinabadi-Bidgoli; Kasra Moeinabadi-Bidgoli; Malihe Rezaee; Malihe Rezaee; Hamidreza Rismanchi; Mohaddese Malek Mohammadi; Amirhesam Babajani (Frontiers in Cell and Developmental Biology, 2022)
Mesenchymal stem cells (MSCs), as adult multipotent cells, possess considerable regenerative and anti-neoplastic effects, from inducing apoptosis in the cancer cells to reducing multidrug resistance that bring them up as an appropriate alternative for cancer treatment. These cells can alter the behavior of cancer cells, the condition of the tumor microenvironment, and the activity of immune cells that result in tumor regression. It has been observed that during inflammatory conditions, a well-known feature of the tumor microenvironment, the MSCs produce and release some molecules called “antimicrobial peptides (AMPs)” with demonstrated anti-neoplastic effects. These peptides have remarkable targeted anticancer effects by attaching to the negatively charged membrane of neoplastic cells, disrupting the membrane, and interfering with intracellular pathways. Therefore, AMPs could be considered as a part of the wide-ranging anti-neoplastic effects of MSCs. This review focuses on the possible anti-neoplastic effects of MSCs-derived AMPs and their mechanisms. It also discusses preconditioning approaches and using exosomes to enhance AMP production and delivery from MSCs to cancer cells. Besides, the clinical administration of MSCs-derived AMPs, along with their challenges in clinical practice, were debated.